Prevalence of Vitamin D Inadequacy among Postmenopausal Women (Medical Forum Monthly, 2024)
Objective: To evaluate serum vitamin D levels and factors related to vitamin D inadequacy in postmenopausal women.Study Design: Observational Cross -sectional studyPlace and duration of Study: This study was conducted in Outpatient departments of Obstetrics & Gynaecology and Orthopedics& Traumatology, Khyber Teaching Hospital, Peshawar from Dec 2011 to Nov 2012.Materials and Methods: During the study period, 200 postmenopausal women presenting to Orthopedics and Gynecology outpatient departments of Khyber Teaching Hospital were randomly recruited to the study. Women with active liver and /or kidney disease and those taking drugs affecting calcium and vitamin D metabolism were excluded from the study.Serum Vitamin D levels were analyzed and were categorized as adequate (more than 30 ng/ml), insufficient( 20–30 ng/ml), mild deficiency(10–20 ng/ml), moderate (5–10 ng/ml) and severe (< 5 ng/ml).Results: The study included 200 postmenopausal women. Mean age was 58 years with a mean BMI of 24.3 kg/m2.Mean Vitamin D levels were 14.7 ng/ml with a range of 4-62 ng/ml.Vitamin D levels were adequate in only 19% of women. Twenty two percent had insufficient levels. Vitamin D deficiency was present in 59 % of postmenopausal women. Thirty three percent had mild deficiency while 21 % had moderate deficiency. Five percent of women were severely deficient.Conclusion: More than half ofpostmenopausal women in our province have vitamin D deficiency underscoring the need for vitamin D supplementation in this vulnerable population. Prevention and early detection of hypovitaminosis D is the key to reduce the incidence of osteoporosis among postmenopausal women.